Roots [videorecording (DVD)] - Coleman, Chad; Corinealdi, Emayatzy, 1980-; Fishburne, Laurence, III, 1961-; Goode, Matthew, 1978- (A&E Television Networks, LLC, 2016)
The gripping story is told through four generations, from the capture of Kunta Kinte in Africa to his transport to Colonial America in brutal conditions through successive generations fighting to win their freedom in the Civil War.